Spatial and Contamination-Dependent Electrical Properties of Carbon Nanotubes - Cathren Gowenlock (Nano Letters, 2018)
Two-point probe and Raman spectroscopy have been used to investigate the effects of vacuum annealing and argon bombardment, on the conduction characteristics of MWCNTs. Surface contamination has a large effect on the two-point probe conductivity measurements resulting in inconsistent and non-reproducible contacts as well as enhancing the electric field under the contacts resulting from overlapping depletion regions when probe separations are small (< 4 μm) causing very high resistances. Annealing at 200 °C and 500 °C reduced the surface contamination on the MWCNT, but high resistance contacts still did not allow intrinsic conductivity measurements of the MWCNT. The high resistance measured due to the overlapping depletion regions was not observed after annealing to 500 °C. Argon bombardment reduced the surface contamination more than vacuum annealing at 500 °C but caused a slight increase in the defects concentration, enabling the resistivity of the MWCNT to be calculated, which is found to be dependent on the CNT diameter. The observations have significant implications for future CNT-based devices.